Relationship Between Social Support, Affective Commitment, and Employee Engagement - Setiabudhi Setiabudhi; Cholichul Hadi; Seger Handoyo (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
The purpose of this study was to examine the predictive effect of social support and affective commitment on employee engagement. It is hypothesized that social support will be positively related to employee engagement, and this relationship will be transmitted through affective commitment. Survey data were collected from 115 employees who are registered as active students at Universitas 45 Surabaya. The results of multiple regression analysis show a positive relationship between social support and employee engagement mediated by affective commitment. This finding can explain to companies that employee engagement can be effective by ensuring that employees perceive their organization as providing social support by increasing employees' affective commitment.